KEDUDUKAN HUKUM PERWALIAN PERNIKAHAN DALAM PERSPEKTIF HUKUM ISLAM DAN PERDATA (STUDI KOMPERATIF) - dawam, fahrul (Musyarokah: Jurnal Hukum dan Ekonomi Islam, 2024)
Abstract The Prophet Muhammad SAW has advised his followers to follow all his sunnahs, one of the sunnahs is to carry out marriages for those who fulfill the terms and conditions. And in carrying out a marriage, a competent person is needed who has authority over someone under his control to guide and represent him in all matters, especially matters of benefit in the marriage process. The position of guardianship (guardian) in a marriage is important for achieving a good and valid marriage, both in civil law and Islamic law. In this study, the author found similarities and differences regarding marital guardianship in Islamic and civil law, among the similarities between the two is that marital guardianship is a person's power over the person they control to handle all matters including marriage. Meanwhile, the difference between the two is that guardianship in marriage in Islam is one of the pillars, whether for someone who is an adult or not, whereas in civil law, guardianship in marriage is not one of the pillars for someone who is an adult (men are 18 years old and women are 15 years), In contrast, someone who is not yet an adult must have a guardian, namely by asking permission from his guardian to carry out a valid marriage.. Keywords: guardianship,wedding